Shared reality of the abusive and the vulnerable: the experience of aging for parents living with abusive adult children coping with mental disorder. (November 2014) - Band-Winterstein, Tova; Smeloy, Yael; Avieli, Hila
ABSTRACT Background: Increasing numbers of aging parents are finding themselves in the role of caregiver for their mentally ill adult child due to global deinstitutionalization policy. The aim of this paper is to describe the daily aging experience of parents abused by an adult child with mental disorder and the challenges confronting them in this shared reality. Methods: Data collection was performed through in-depth semi-structured interviews with 16 parents, followed by content analysis. Results: Three major themes emerged: (a) old age as a platform for parent's vulnerability facing ongoing abuse; (b) "whose needs come first?" in a shared reality of abusive and vulnerable protagonists; (c) changes in relationship dynamics. Conclusions: Old age becomes an arena for redefined relationships combining increased vulnerability, needs of both sides, and its impact on the well-being of the aging parents. This calls for better insights and deeper understanding in regard to intervention with such families.